2022
DOI: 10.1200/jco.2022.40.16_suppl.6535
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of systematic screening for unmet social determinants of health (SDoH) needs and associated resource utilization in ambulatory oncology.

Abstract: 6535 Background: Addressing unmet SDoH needs may reduce interruptions to cancer care caused by ED visits and hospitalizations (EDH). We aimed to determine feasibility of systematic screening for unmet patient-reported SDoH needs within a large tertiary academic comprehensive cancer center and association of unmet needs with EDH. Methods: We conducted a cross-sectional analysis of SDoH needs among new oncology patient (pts) consults from 5/15-9/21 at Dana-Farber Cancer Institute (DCFI). Pts completed an intake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Prior studies demonstrate that collecting patient‐reported data can improve health outcomes, reduce adverse events, and expand access to care. 4 , 5 , 6 Specifically, some cancer centers have developed enterprise‐wide 7 , 8 , 9 or clinic‐specific 10 intake forms to collect pertinent patient‐reported data prior to a patient's first visit. Equitable participation in these data collection efforts is essential for ensuring that all patients receive patient‐centered care.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies demonstrate that collecting patient‐reported data can improve health outcomes, reduce adverse events, and expand access to care. 4 , 5 , 6 Specifically, some cancer centers have developed enterprise‐wide 7 , 8 , 9 or clinic‐specific 10 intake forms to collect pertinent patient‐reported data prior to a patient's first visit. Equitable participation in these data collection efforts is essential for ensuring that all patients receive patient‐centered care.…”
Section: Introductionmentioning
confidence: 99%